Assessment of pedestrian-level wind conditions in severe cold regions of China. (1st May 2018) - Shui, Taotao; Liu, Jing; Yuan, Qing; Qu, Yang; Jin, Hong; Cao, Junliang; Liu, Lin; Chen, Xin
Abstract: Pedestrian-level wind environment in urban areas has a significant impact on the quality of urban dwellers' daily life. For pedestrian-level wind studies in severe cold regions, the cooling effect of wind and related thermal discomfort in winter is quite significant. However, thermal effects of wind are not considered in most wind comfort studies and wind comfort generally only refers to the mechanical effects of wind on people. Therefore, particular consideration is given to the chilling effect of wind on exposed skin and risk of frostbite in winter, and a wind chill criterion based on the wind chill temperature is proposed in this study. The pedestrian-level wind conditions in seven representative residential areas summarized from cities in severe cold regions of China are assessed based on the wind mechanical comfort criterion of NEN 8100 and the wind chill criterion. CFD simulations are performed to provide the pedestrian-level aerodynamic information, and the simulation results are validated by wind tunnel experiments. The assessment results show that the wind mechanical comfort or wind chill criterion need to be combined when assessing the wind conditions in severe cold regions. From the perspective of wind mechanical comfort and wind chill, the multi-storey residential areas with hybrid-type and the enclosed-type layout are recommended in severe cold regions. Moreover, a strict control of building height in residential areas is important to improve the pedestrian-level wind mechanical comfort, but not very helpful to reduce the occurrence of frostbite in winter. Highlights: Proposing a wind chill criterion to evaluate the wind conditions in severe cold regions. Conducting CFD simulations to assess the pedestrian-level wind conditions in residential areas with typical layouts. The multi-storey residential areas with hybrid-type and the enclosed-type layout are recommended in severe cold regions. A strict control of building height is more helpful to improve the wind mechanical comfort than to reduce the wind chill.